Emerging non-viral vectors for gene delivery - Wang, Chenfei; Pan, Chaolan; Yong, Haiyang; Wang, Feifei; Bo, Tao; Zhao, Yitong; Ma, Bin; He, Wei; Li, Ming (Journal of nanobiotechnology, 2023)
Gene therapy holds great promise for treating a multitude of inherited and acquired diseases by delivering functional genes, comprising DNA or RNA, into targeted cells or tissues to elicit manipulation of gene expression. However, the clinical implementation of gene therapy remains substantially impeded by the lack of safe and efficient gene delivery vehicles. This review comprehensively outlines the novel fastest-growing and efficient non-viral gene delivery vectors, which include liposomes and lipid nanoparticles (LNPs), highly branched poly(β-amino ester) (HPAE), single-chain cyclic polymer (SCKP), poly(amidoamine) (PAMAM) dendrimers, and polyethyleneimine (PEI). Particularly, we discuss the research progress, potential development directions, and remaining challenges. Additionally, we provide a comprehensive overview of the currently approved non-viral gene therapeutics, as well as ongoing clinical trials. With advances in biomedicine, molecular biology, materials science, non-viral gene vectors play an ever-expanding and noteworthy role in clinical gene therapy.